2021
DOI: 10.3389/fonc.2021.656229
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Endothelial Cells Relies on a Ferroptosis-Like Mechanism: Novel Perspectives in Management of Angiogenesis and Cancer Therapy

Abstract: The activation of endothelial cells (ECs) is a crucial step on the road map of tumor angiogenesis and expanding evidence indicates that a pro-oxidant tumor microenvironment, conditioned by cancer metabolic rewiring, is a relevant controller of this process. Herein, we investigated the contribution of oxidative stress-induced ferroptosis to ECs activation. Moreover, we also addressed the anti-angiogenic effect of Propranolol. We observed that a ferroptosis-like mechanism, induced by xCT inhibition with Erastin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 81 publications
3
24
0
Order By: Relevance
“…Recently, Lopes-Coelho (2021) showed that the angiogenic process may rely on a ferroptosis-like mechanism in endothelial cells, promoted by the blockage of xCT-related cystine cellular uptake [ 39 ]. Cystine avoids ferroptosis and increases glutathione availability, which avoids the angiogenic switch and promotes vessel stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lopes-Coelho (2021) showed that the angiogenic process may rely on a ferroptosis-like mechanism in endothelial cells, promoted by the blockage of xCT-related cystine cellular uptake [ 39 ]. Cystine avoids ferroptosis and increases glutathione availability, which avoids the angiogenic switch and promotes vessel stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs: ATCC ® CRL-1730™) were obtained from American Type Culture Collection (ATCC) and cultured in Endothelial Cell Growth Basal Medium-2 (EBM-2: CC-3156, Lonza Bioscience, Basel, Switzerland) supplemented with EGM-2 SingleQuots Supplements (CC-4176, Lonza Bioscience), at 37 °C in a humidified environment of 5% CO 2 , according to previous experience [ 39 ]. HUVECs (2 × 10 5 cells/well) were plated in 6-well plates and exposed to cysteine (0.2, 0.4 and 0.8 mM) and cystine (0.1, 0.2 and 0.4 mM) for 6 and 24 h [ 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Calpain inhibitor (PD151746) blocked these effects. VE-cadherin participates in ferroptosis-like mechanism by increasing endothelial cell junction gaps ( Lopes-Coelho et al, 2021 ). Furthermore, E-cadherin, analog of VE-cadherin, has been shown to regulate ferroptosis through activating intracellular NF2-YAP signaling pathway ( Wu et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased degradation of VE-cadherin has also been found to cause cerebrovascular dysfunction ( Bhatia et al 2021 ), ventilation-induced lung vascular hyperpermeability ( Jiang L. et al 2021 ) and lung edema ( Cowan et al, 2010 ). Previous studies have recently established that increase in VE-cadherin internalization occurred in erastin-induced endothelial cell ferroptosis ( Stockwell et al, 2017 ; Lopes-Coelho et al, 2021 ). E-cadherin, analog of VE-cadherin, regulates ferroptosis ( Wu et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EC treatment with erastin, an inhibitor of xCT, at a non-lethal level promotes EC proliferation, migration, and vessel-like structures formation, concomitantly with a reduction of GSH and an increase in ROS. The dual therapy using propranolol, which reverts the erastin-dependent activation of ECs, and chrysin to induce cytotoxic to cancer cells, has been proposed [ 100 ].…”
Section: Rewiring Of Endothelial Metabolism In Cancermentioning
confidence: 99%